Orthosiphon stamineus (Java Tea) - Jolius, Gimbun; Sook, Fun Pang; M. M., Yusoff (Academic Press, 2019)
Orthosiphon stamineus has long been used in traditional medicine in East India, Indo China, South East Asia, and tropical regions of Australia where the plant is usually found. This chapter provides a review of preclinical and clinical trials related to the diuretic, antidiabetic, antihypertensive, nephroprotective, hepatoprotective, gastroprotective, antiproliferative, and anticancer activities of O. stamineus. In addition, toxicity and possible interactions with other drugs or supplements are outlined.